2009
DOI: 10.1016/j.cageo.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

MOIRA-PLUS: A decision support system for the management of complex fresh water ecosystems contaminated by radionuclides and heavy metals

Abstract: Abstract. The accidental release of radioactive substances into the environment leads to the necessity of applying suitable countermeasures for the restoration of the polluted environment. However, despite their obvious benefits, such interventions may result in detrimental effects of economic, ecological and social nature that must be carefully evaluated.MOIRA-PLUS is a PC-based user-friendly, Computerised Decision Support System (CDSS) that helps decision makers to choose optimal countermeasure strategies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Decision support theory, methods, and algorithms have been discussed by many researchers in the literature [36][37][38][39][40][41][42][43]. In this study, a decision support system for risk assessment of heavy metal pollution in farmland soils (DSS-RAHMP) is proposed ( Figure 1) and can be used for common risk assessment practices for heavy metal pollution in farmland soils.…”
Section: Framework For Decision Support Of Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision support theory, methods, and algorithms have been discussed by many researchers in the literature [36][37][38][39][40][41][42][43]. In this study, a decision support system for risk assessment of heavy metal pollution in farmland soils (DSS-RAHMP) is proposed ( Figure 1) and can be used for common risk assessment practices for heavy metal pollution in farmland soils.…”
Section: Framework For Decision Support Of Risk Assessmentmentioning
confidence: 99%
“…With the rapid growth of heavy metal pollution monitoring data, an intelligent management information system should be established by using current advanced information technologies to effectively integrate massive amounts of data for data sharing, data mining [35], and decision support [36,37]. In this study, a decision support system based on web-based GIS (WebGIS) for risk assessment of heavy metal pollution in farmland soils is constructed and aims to assess the potential safety risk in farmland soils.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other DSSs to support decisions in the case of radioactive contaminations, more recently MOIRA ( [11], [12]) and its newest version MOIRA-PLUS ( [13]) provide support for the identification of optimal remedial strategies to restore water systems after accidental introduction of radioactive substances.…”
Section: The Needs Of a Nuclear Dssmentioning
confidence: 99%
“…In the second period, the decision aiding component, the usefulness and applicability of the hydrological model chain and the application of the MOIRA system (Monte et al, 2009) for the long term contamination of water catchments were demonstrated by the end users. Further demonstrations focused on small scale applications dealing with releases other than from a nuclear power plant and the two handbooks on assisting in the management of contaminated food production systems and contaminated areas.…”
Section: Demonstrationsmentioning
confidence: 99%